THE PROBLEM OF OBTAINING CONCRETES WITH HIGH OPERATION PROPERTIES - Pshinko, O. M.; Krasniuk, A. V.; Punahin, V. M. (Science and Transport Progress, 2004)
The work provides analysis of the problems, connected with obtaining high-strength concretes for ring-like and tubular non-armatured constructions and shows a possibility of obtaining a material, capable of enduring significant pull tensions in applications of a complex of technological actions. This will allow realizing the developed technology in manufacture of ringular and tubular structures for non-head and small-head water courses.